The bidirectional relationship between L1 and L2: Effects on event conceptualization and narrative discourse - Erciyes, Aslı Aktan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The present study intended to answer two major research questions: 1) Whether intense exposure to a second language (L2) affects first language (L1) narrative skills of 5- and 7-year old children, and 2) whether learning a second language that is typologically different from the first affects their motion event conceptualization patterns? These questions were investigated by comparing bilingual children with their monolingual peers in terms of their narrative performance and motion event description patterns. In addition, children’s executive functioning and vocabulary performance were assessed. One-hundred and twelve 5- and 7-year- monolingual (L1, Turkish) (N=61) and bilingual (L1, Turkish; L2, English) (N=51) children participated in the study. Results showed that development of L1 narrative skills of the bilingual groups advanced at a slower pace compared to monolinguals and that there is a monolingual advantage in certain aspects including narrative quality and linguistic complexity. Motion event conceptualization patterns in both elicited L1 narratives and event descriptions showed that there is an influence of learning L2-English which is typologically different than L1-Turkish. Investigations of L2 narratives and motion event descriptions suggested a bidirectional relationship between L1 and L2. The study also confirmed bilingual advantage on inhibition and cognitive flexibility components of executive functioning. Results inform us about the early interactions between L1 and L2 for motion event conceptualization and narrative discourse.
Keywords: Second language acquisition.; Native language.; Narrative inquiry (Research method)